Mechanical design : an integrated approach - Ugural, Ansel C (McGraw-Hill/Higher Education, 2004)
An Integrated Approach provides a comprehensive, unified approach to the subject of machine element design for Mechanical Engineering students and practicing engineers. The author's expertise in engineering mechanics is demonstrated in Part I (Fundamentals), where readers are given an exceptionally strong treatment of the design process, stress & strain, deflection & stiffness, energy methods, and failure/fatigue criteria. Advanced topics in mechanics (marked with an asterisk in the Table of Contents) are provided for optional use. The first 8 chapters provide the conceptual basis for Part II (Applications), where the major classes of machine components are covered. Optional coverage of finite element analysis is included, in the final chapter of the text, with selected examples and cases showing FEA applications in mechanical design.